AN ANALYSIS OF CHARACTER DIFFERENCES AMONG ENGLISH EDUCATION STUDENTS AT NIAS UNIVERSITY: A COMPARISON BETWEEN THE 2022 AND 2024 COHORTS - Laoli, Adieli; Hulu, Lince Kristi; Zebua , Mega Rohani; Harefa , Sevtryani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research examines the character of English Education students at Nias University, specifically focusing on the definition of character, the importance of good character in student life, and emphasizing the aspects of discipline and politeness. Character is defined as noble values that are manifested in a person's behavior and actions, shaping their identity and morality. Good character is crucial for students, as it supports academic success, fosters responsible individuals, and prepares them to become integral members of society. Character discipline is a vital aspect that encompasses punctuality, responsibility, and dedication in fulfilling duties and obligations. Polite character involves courteous, respectful, and empathetic behavior in interactions with lecturers, fellow students, and the surrounding environment. This research aims to understand the perceptions of English Education students at Nias University regarding the importance of character, as well as to identify factors influencing the development of their character in terms of discipline and politeness. The research findings are expected to provide recommendations for developing more effective character education programs to enhance the quality of English Education students at Nias University.